Pengaruh Motivasi Dan Gaya Kepemimpinan Terhadap Kinerja Karyawan Melalui Kepuasan Kerja Karyawan Sebagai Variabel Intervening Di Pd Bpr Bkk Wonosobo - Dewi, Kristiana; Sutrischastini, Ary (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2016)
Motivation and leadership styles are variables that affect the performance of the employee, either directly or indirectly through intervening variables such as job satisfaction. Number of respondents in this study 78 people were taken from all employees PD . BPR BKK Wonosobo unless the Board of Directors. Methods of data collection is done by means of a questionnaire that the results are the primary data for further analysis using multiple regression analysis and regression analysis of two lines, using SPSS.17 program. The results of analysis show that the variable motivation and leadership styles, both individually and together, the positive and significant effect on performance. Variable motivation and leadership styles together positive and significant effect on job satisfaction. Variable motivation, leadership style and job satisfaction together positive and significant effect on performance. Variable motivation and leadership styles each have a positive and significant impact indirectly on performance, through the variable job satisfaction. Through the analysis of the results of the adjusted determination coefficient (adjusted R 2) of the analytical model regesi two pathways by which performance is affected by motivation, leadership style and job satisfaction, it is known that 62.1 % of the variation in performance can be explained by the variable employee motivation, leadership style and satisfaction work; while 37.9 % is explained by other factors outside the model. Key word : Motivation, leadership style, job satisfaction, performance